Microwave-Induced Synthesis and Multifunctional Characterisation of Co (II), Ni (II), Cu (II) and Zn (II) Complexes of a Methoxy-Substituted Hydrazide Ligand - Kalpana Shukla; Samit Kumar; Dinesh Kumar Mishra; Harendra Kumar (The Bioscan, 2025)
This research work delineates the application of microwave-assisted synthesis, the investigation of the structural properties, the analysis of the magnetic behavior, the study of the heat resistance and the antimicrobial testing of a new hydrazide ligand, 4-methoxybenzylidene isonicotinoyl hydrazide (HL), and its complexes with ions. Microwave irradiation not only enabled the very fast synthesis of ligands and metal complexes but also provided a lot of advantages over the classic heating methods such as better quality and purity of the products. The ligand HL was found to be bidentate coordinated through azomethine nitrogen and carbonyl oxygen, which led to the formation of stable bis-chelated complexes having predominantly octahedral geometries confirmed by FTIR, UV-Vis, elemental analysis, molar conductivity and magnetic susceptibility.The thermal investigations indicated that strong coordination and high stability were the reasons for the progressive decomposition, resulting in stable oxides of the metal residues. The magnetic investigations revealed high-spin complexes, typical paramagnetic behaviour, and diamagnetic. Antimicrobial testing demonstrated the synergistic effects of metal complexes on antibacterial and antifungal activities, particularly for the species. Molecular docking studies performed against DNA gyrase B confirmed the results, indicating that the complexes had stronger binding energies and more favourable interactions when compared to the free ligand. As a result, the results validate microwave-assisted hydrazide metal coordination chemistry as a dependable and efficient way to produce transition metal complexes that are both structurally strong and bioactive. KEYWORDS: microwave synthesis, hydrazide ligand, transition metal complexes, octahedral geometry, antimicrobial activity, docking.